Exploration of workforce changes in integrated chronic care: findings from an interactive and emergent research design - Busetto, Loraine (PLOS ONE, 2017)
Introduction Integrated care interventions introduced in response to the increased demand for long-term care entail profound changes to the health workforce. This exploratory study aims to provide an overview of the workforce changes implemented as part of integrated chronic care interventions. Methods An interactive and emergent research design was used consisting of a literature review, qualitative expert questionnaires and case reports. We defined integrated care as interventions targeting at least two of the six Chronic Care Model components. Workforce changes were defined as those changes experienced by clinical and non-clinical staff responsible for public and individual health intervention. Results Seven workforce changes were identified: (1) nurse involvement, (2) multidisciplinary staff, (3) multidisciplinary protocols/pathways, (4) provider training, (5) case manager/care coordinator, (6) team meetings, and (7) new positions. Most interventions included more than one of these workforce changes. Conclusion The results of this study provide detailed insights into the current implementation of workforce changes in integrated care interventions and thereby pave the way for further investigations into the relative effectiveness of different workforce changes within the scope of complex interventions. Advancing knowledge in this area is essential for fostering health systems’ capacity to cope with the challenges related to the current demographic and epidemiological trends.
Gesehen am 05.06.2018